Correlation of irisin with lipid profile in type 2 diabetes mellitus - Wahengbam Diana Devi; Oinam Prabita Devi; Ursula Khwairakpam; Takhelmayum Paras Singh (Asian Journal of Medical Sciences)
Background: Irisin, a novel adipo-myokine, improves insulin sensitivity by browning of white adipose tissue and also promotes pancreatic β-cell proliferation. Irisin was seen to have great therapeutic potential in treating type 2 diabetes mellitus (T2DM) patients.